2020
DOI: 10.1186/s12909-020-02029-0
|View full text |Cite
|
Sign up to set email alerts
|

When investigating depression and anxiety in undergraduate medical students timing of assessment is an important factor - a multicentre cross-sectional study

Abstract: Background: Symptoms of depression and anxiety experienced by undergraduate medical students have become a prominent concern. Evidence about students' depression and anxiety including prevalence, trajectory during medical education, gender differences and comparisons with age-matched peers is conflicting. However few studies of medical students' mental health specify the precise time of assessment. Proximity to examinations may be relevant. Precise identification of the time of data collection might help expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…11 There is growing concern over the mental health of the future clinicians as it may directly impact their professional commitment. 12 Studies have been conducted in Pakistan 13,14 and Saudi Arabia 15 to assess stress levels in dental and medical students. However, there is scarce literature regarding the psychological well-being of health sciences students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There is growing concern over the mental health of the future clinicians as it may directly impact their professional commitment. 12 Studies have been conducted in Pakistan 13,14 and Saudi Arabia 15 to assess stress levels in dental and medical students. However, there is scarce literature regarding the psychological well-being of health sciences students.…”
Section: Introductionmentioning
confidence: 99%
“… 11 There is growing concern over the mental health of the future clinicians as it may directly impact their professional commitment. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Parallel to prior studies, a self-report methodology can be a useful approach to collect data about individuals' perception of mental health. Said perception, especially regarding mental wellbeing, can be time dependent [2]. We would like to praise Fletcher et al in their commitment towards this research by sending the questionnaire, with weekly reminders, to all enrolled students across all years [1].…”
Section: Dear Editormentioning
confidence: 99%
“…We believe it would be interesting to see how students' attitudes towards disclosure may vary at different time points within the same academic year, particularly during final examinations. Anxiety and depression have a higher prevalence rate in students where examinations are imminent, highlighting the importance for research to specify the time of year, alongside academic class, when exploring student mental wellbeing [2].…”
Section: Dear Editormentioning
confidence: 99%
“…One aspect of the educational environment that was not made clear in the study methodology was the temporal relationship between examination periods and questionnaire completion. Thiemann et al 4 recently demonstrated a significant increase in clinical depressive and anxiety symptoms in final year medical students whose clinical examinations were within two months compared to students outside of this examination period. This highlights the need for a longitudinal assessment to identify whether the contribution of stressors to depression, anxiety, or stress symptoms is transient or protracted.…”
mentioning
confidence: 98%